2023
DOI: 10.1016/j.prosdent.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yttria content and surface treatment on the strength of translucent zirconia materials

Abstract: Zirconia first gained attention as an engineering ceramic in the 1970s and began to be used in prosthodontics in the late 1990s. [1][2][3] Zirconia exhibits polymorphism, existing in cubic, tetragonal, and monoclinic forms. A martensitic phase transformation from tetragonal to monoclinic (t/m) zirconia forms is accompanied by a 4% increase in volume. However, a small amount of controlled expansion can decrease crack propagation, thereby making a material tougher through a process called transformation tougheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
3
0
4
Order By: Relevance
“…Este endurecimiento le proporciona su alta tenacidad a la fractura; sin embargo, la desventaja que presenta es la opacidad, debido a la presencia de alúmina. Este material se le agregó para ayudar a prevenir la formación de poros y estabilizar el zirconio tetragonal 4 , 6 , 16 .…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Este endurecimiento le proporciona su alta tenacidad a la fractura; sin embargo, la desventaja que presenta es la opacidad, debido a la presencia de alúmina. Este material se le agregó para ayudar a prevenir la formación de poros y estabilizar el zirconio tetragonal 4 , 6 , 16 .…”
Section: Resultados Y Discusiónunclassified
“…En la primera generación, las zirconias utilizadas en odontología, en su mayoría, contenían 3 mol% de itria (3Y) y 0,25% de peso de alúmina, material conocido como zirconio opaco. Este proporciona una resistencia significativamente mayor y está indicado para restauraciones posteriores de la boca 4 , 5 . En la segunda generación, se presentó una reducción de la concentración de alúmina y se realizó la sinterización a una alta temperatura del 3 Y, para lograr menor opacidad; sin embargo, este material carece de translucidez.…”
Section: Introductionunclassified
“…Translucency of zirconia is mainly dependent on light scattering and thickness [2]. Also, yttria content, phase composition, grain size, number of firings, sintering temperature, and coloring method are crucial factors that affect the translucency and color of zirconia [3][4][5]. Translucency was determined by spectrophotometers which measure the spectral reflectance of an object one wavelength at a time and converts it into numerical form [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study showed that the stability of the crown-abutment connection in implants can be dependent on the “ferrule effect”, analogous to natural teeth, and consequently increases in the presence of ferrulization [ 9 ]. The fixation data published is as follows: analyzing the effect of contamination of the bond surface [ 10 , 11 , 12 ], the cement type and abutment height [ 13 ], abutment platform configuration [ 14 ], airborne-particle abrasion by using alumina [ 15 ] or silanisation and laser pretreatment [ 16 ] on retention force of the restoration. In addition, it is possibly to be expected that the adhesive interface behavior between the implant surface, the luting agent, and the bond surface of the ceramic restoration could be meaningful for the stabilization of the ceramic restoration.…”
Section: Introductionmentioning
confidence: 99%